2017
DOI: 10.1111/jdv.14612
|View full text |Cite
|
Sign up to set email alerts
|

Scalp hypothermia as a preventative measure for chemotherapy‐induced alopecia: a review of controlled clinical trials

Abstract: Chemotherapy-induced alopecia (CIA) is a temporary, yet psychologically devastating form of hair loss that affects 65% of patients receiving cancer chemotherapy. In the 1970s, scalp hypothermia was introduced as a preventative measure against the development of CIA. Numerous studies provide evidence for the effectiveness of scalp cooling to prevent CIA, although results varied because of differences in chemotherapy regimen, cooling technique, mode of administration and patient factors. However, many of the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
0
25
0
3
Order By: Relevance
“…In vitiligo, dissatisfaction to therapies is due to complexity of a multifactorial disease whose precise aetiology is still unclear even if T cell-mediated autoimmunity trigged by oxidative stress is recognized as the prevalent mechanism for the onset of white patches. [48] Permanent oxidative disequilibrium caused by an intrinsic defect as in vitiligo skin may also prevent melanocyte regeneration and lead to a vicious circle. In fact, even if several studies revealed the presence of some melanocytes in depigmented skin, [49][50][51] it is conceivable that the persistence of a hostile environment does not allow the complete return of functional melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In vitiligo, dissatisfaction to therapies is due to complexity of a multifactorial disease whose precise aetiology is still unclear even if T cell-mediated autoimmunity trigged by oxidative stress is recognized as the prevalent mechanism for the onset of white patches. [48] Permanent oxidative disequilibrium caused by an intrinsic defect as in vitiligo skin may also prevent melanocyte regeneration and lead to a vicious circle. In fact, even if several studies revealed the presence of some melanocytes in depigmented skin, [49][50][51] it is conceivable that the persistence of a hostile environment does not allow the complete return of functional melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…There were 18 trials included in the review, with different scalp cooling techniques – ranging from older and less complex cooling caps to digitally controlled machines. 49 Scalp cooling machines from Paxman and Dignitana have been approved by the Food and Drug Administration (FDA), and have been incorporated into the NCCN guidelines for breast cancer patients.…”
Section: Understanding Chemotherapy-induced Alopeciamentioning
confidence: 99%
“…Those with intradermal scalp temperature lower than 18 °C are more likely to have better hair protection with scalp cooling. 49 , 52 …”
Section: Understanding Chemotherapy-induced Alopeciamentioning
confidence: 99%
“…Shah et al 1 provide a careful analysis of clinical trials with the highest level of evidence. Authors confirmed the efficacy of scalp hypothermia in reducing the rate of CIA, but it depends on therapeutic agents and dosage schedules.…”
mentioning
confidence: 99%
“…To the editor, We read with great interest the guideline for the treatment of cutaneous lupus erythematosus (CLE) elaborated by the European Dermatology Forum in cooperation with the European Academy of Dermatology and Venereology published in the Journal of the European Academy of Dermatology and Venereology in March 2017. 1 A therapeutic guide for CLE is absolutely necessary to decide the best management of our patients. Nevertheless, we would like to point out important aspects regarding the role of laser therapy in patients with CLE.…”
mentioning
confidence: 99%